Effective gravitational couplings of higher-rank supersymmetric gauge theories - John, Renjan Rajan (2022)
When placed on four-manifolds, N = 2 gauge theories couple to topological invariants of the background via two functions A and B. General considerations allow for these functions to be fixed in terms of the Coulomb moduli and other parameters in the theory, but only up to multiplicative factors about which little is known. We extend earlier work on the microscopic study of these functions in the Ω-background to N = 2* gauge theories with higher-rank U(N) gauge groups. We complement this analysis by carrying out a perturbative study of these functions. This allows us to determine the manner in which these multiplicative factors scale with the rank of the gauge group and the mass of the adjoint hypermultiplet.